La esclavitud asiática en el virreinato de la Nueva España, 1565-1673 - Oropeza Keresey, Déborah (El Colegio de México, A.C., 2011)
When a continuous communication was established between the center of the Viceroyalty of New Spain and its Asian Audiencia in the Philippines thanks to the Nao of China, there appeared a transpacific migration of Asian slaves travelling to the center of the viceroyalty between 1656 and 1673. In this paper, I analyze the evolution and characteristics of this type of migration, including the various procedures of slave transportation, the scope of the migratory movement, as well as the different origins of Asian slaves. I also examine the kind of work undertaken by Asian slaves in the center of the Novohispanic viceroyalty. Finally, I consider the freedom process of these slaves, which took place during the second half of the 17th century.